Supporting Preemptive Multitasking in Wireless Sensor Networks - Emanuele Lattanzi; Valerio Freschi; Alessandro Bogliolo (International Journal of Distributed Sensor Networks)
Supporting the concurrent execution of multiple tasks on lightweight sensor nodes could enable the deployment of independent applications on a shared wireless sensor network, thus saving cost and time by exploiting infrastructures which are typically underutilized if dedicated to a single task. Existing approaches to wireless sensor network programming provide limited support to concurrency at the cost of reducing the generality and the expressiveness of the language adopted. This paper presents a java-compatible platform for wireless sensor networks which provides a thorough support to preemptive multitasking while allowing the programmers to write their applications in java. The proposed approach has been implemented and tested on top of VirtualSense, an ultra-low-power wireless sensor mote providing a java-compatible runtime environment. Performance and scalability of the solution are discussed in light of extensive experiments performed on representative benchmarks.